Clinical evaluation of glutathione concentrations after consumption of milk containing different subtypes of β-casein: results from a randomized, cross-over clinical trial. Issue 1 (December 2015) - Deth, Richard; Clarke, Andrew; Ni, Jiayi; Trivedi, Malav
Abstract This study reports the plasma glutathione concentrations in a double-blind, randomized, controlled, 2 × 2 cross-over study in which healthy participants consumed conventional milk (2 × 250 mL per day) containing both A1 and A2 types of β-casein, or milk containing only A2 type β-casein. Beta-casomorphin-7 (BCM-7), a peptide uniquely derived from the A1 type of β-casein, was previously reported to downregulate glutathione expression in human gut epithelial and neuronal cell lines by limiting cysteine uptake. The current human study demonstrates that consumption of milk containing only A2 β-casein was associated with a greater increase in plasma glutathione concentrations compared with the consumption of milk containing both β-casein types, and did not increase plasma BCM-7 concentrations compared with the washout diet in the study participants. Thus, milk containing only A2 β-casein and not A1 β-casein has the potential to promote the production of the antioxidant glutathione in humans. Clinical Trial Registration ClinicalTrials.gov; identifier:NCT02406469